Antimicrobial activity of a propolis adhesive formulation on different oral pathogens - Rafael Tomaz Gomes; Karina Imaculada Rosa Teixeira; Maria Esperanza Cortés; Vagner Rodrigues Santos (Universidade Estadual de Campinas, 2016)
Recent studies have shown that propolis has appreciable antibacterial, antifungal and antiviral actions, as well as cytostatic and antitumoral activity. In light of these studies, the antimicrobial activity of a new adhesive formulation containing propolis was evaluated in this in vitro study. Susceptibility of the oral strains tested (Candida albicans, Candida tropicalis, Streptococcus mutans, Staphylococcus aureus, Enterococcus faecalis, Actinomyces israelli, Actinobacillus actinomycetemcomitans) was evaluated using the agar diffusion method with different concentrations of propolis (5, 10, 15 and 20%). All of the assayed bacteria and fungi species were susceptible to propolis, with minimum inhibitory concentrations (MIC) ranging from 1.75 to 14.0 µg/ml. The positive results suggest that propolis in this sustained release formulation should be further tested as an alternative therapy of infectious conditions of the oral cavity, such as denture stomatitis and periodontitis. However, in vivo studies of the effect of this new adhesive formulation of propolis are needed to determine its possible effects on the oral mucosa.